Proceso de atención de enfermería en gestante de 34 años con preeclampsia severa. - Huacon Galarza, Ivette Elizabeth (2020)
Severe preeclampsia is the increase in blood pressure that can appear at 20 weeks of gestation, in turn, it can affect many organs, liver and kidneys, has proteinuria greater than 5 grams, may present headache, generalized edema. In addition, pre-eclampsia in pregnant women, its mortality is high, this is caused by intrauterine growth retardation and premature delivery. Women with this pathology can present severe problems such as; placental abruption, kidney failure, liver failure, acute lung edema. In order to develop a nursing process to be able to provide better care to women with severe pre-eclampsia, a physical assessment is carried out and through complementary examinations, given results help to provide better care for her recovery.